Stakeholder Analysis of Livestock Beef Demand in Samarinda City - Khoirul Muzaqi; Henny Nuraini; Lucia Cyrilla Eko Nugrohowati Supriyadi Dekrityana; Bramada Winiar Putra (Jurnal Ilmu Pertanian Indonesia, 2025)
Stakeholder analysis is required to determine the roles of each stakeholder in satisfying the meat supply needs of Samarinda City, East Kalimantan Province. The purpose of this study was to assess and categorize the influence and interests of stakeholders in the beef cattle supply chain. Primary data was collected via a survey method, involving questionnaires and interviews with 49 respondents representing farmers, slaughterhouses, government officials, traders, and consumers. A stakeholder analysis was carried out utilizing an influence−interest matrix. The results indicated two main groups: Farmers and traders are major stakeholders in the meat supply chain, with enormous power and interest. In contrast, the mob, which includes customers, the government, and slaughterhouses, has significantly less power and interest. Farmers, as primary producers, and traders, as mediators between customers, play critical roles in guaranteeing meat availability and quality. While the government has regulatory power, its role as a facilitator must be expanded to encourage stakeholder participation. This study provides collaborative solutions for aligning stakeholders' views and objectives with the goal of enhancing beef availability and quality in Samarinda City. Keywords: beef, influence-interest matrix, Samarinda City, stakeholders, supply chain